In vitro plant regeneration via organogenesis of cowpea [ Vigna unguiculata (l.) Walp] - Pellegrineschi, A. (Springer, 1997)
Shoot regeneration via organogenesis was achieved from axenic cowpea [Vigna unguiculata subsp. unguiculata L. (Walp.) Verde.] hypocotyls and cotyledons of advanced breeding lines and varieties. Cotyledons and embryos were excised from green immature pods. The apical parts of the embryos were removed and the hypocotyls were transferred to regeneration media. Cotyledons and hypocotyls were tested on media with gradients of several hormonal and putrescine combinations. Cowpea cotyledons and hypocotyls exhibited a pattern of shoot formation that occurred in three distinct phases. Multiple shoots developed within 45 days from the wounded region of the primary hypocotyl and cotyledons in different media containing a high cytokinin concentration. The induced plant explants were then grown for 20 days in low-intensity light (10 µmol m–2 s –1) on the same medium and numerous shoot buds emerged de novo from the upper part of the hypocotyl and the wounded part of the cotyledons. These buds had no apparent vascular connection with the parent tissues. The plant regeneration capability of this procedure was tested with several cowpea genotypes, five of which (83D442, 86D-1010, 93K-624, Vita 3 and Ife Brown) responded positively with shoot development and were able to form roots and whole plants. Some somaclonal variation was observed.